Testing crops for salinity tolerance: (U. S. Salinity Laboratory, 1993)
The capability of crops to grow on saline soils varies among species and depends on the concentration of salts present in the rootzone and on various environmental and cultural conditions. Ind\formation on the relative tolerance of different crops is essential to the successful management of salt-affected agricultural lands and waters. Results from over 50 years of research have produced salt tolerance data that relate yield reductions of over 90 different crops to soil salinity.